Introduction to Animal Symbolism and Representations in Western Asia - Battini , Laura (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2024)
The five articles that make up the second issue 2024 of Ash Sharq, are reworked versions of some of the lectures held at ASOR in the session ’Thinking, speaking and representing animals in the Ancient Near East’, organised by Laura Battini between 2018 and 2021. They form a coherent whole, all dealing with the symbolic aspects of animals. They should have been published in the first part of the volume which will publish all lectures on animals given at ASOR and which will appear in early 2025. I chose to publish these five lectures here for two reasons. The first is my curiosity. According to the contemporary rules of research, it is preferable to publish a conference in an issue of a journal rather than a book. Although I have already edited 15 issues of it, I have never published a conference in a journal. I was curious to find out why.